Influence of the molecular structure on acoustic absorption in the group or saturated ketones - B. B. LINDE; A. ŚLIWIŃSKI (Archives of Acoustics, 2014)
The results of acoustic investigation into some heterocyclic liquids showed very close relation between ultrasonic absorption and structure of chemical molecules [1, 2, 3].